DETERMINAN MINAT PERILAKU PENGGUNAAN SIA BERBASIS E-COMMERCE (Studi Kasus pada Mahasiswa Akuntansi Fakultas Ekonomi dan Bisnins Universitas Islam Malang Angkatan 2016 dan 2017) - Nurhayati Nurhayati; Maslichah Maslichah; Arista Fauzi Kartika Sari (e_Jurnal Ilmiah Riset Akuntansi, 2021)
The purpose of this study is to obtain empirical evidence regarding the effect of attitudes, subjective norms, perceived behavior control, trust and structural assurance on e-commerce-based accounting information system. This research was conducted at the Faculty of Economics and Business, Islamic University of Malang. Based on the purposive sampling method, a sample of 83 respondents was obtained. Data were collected using a questionnaire through Google Form, then hypothesis testing using multiple regression analysis. Simultaneously attitudes, subjective norms, perceived behavior control, trust, and structural assurance have an positive effect on the behavior interest of e-commerce-based AIS users, partially attitudes, perceived behavior control, and structural assurance not affect e-commerce-based AIS, whereas subjective normsand trust have a effect on e-commerce-based AIS. Keywords: attitudes, subjective norms, perceived behavior control, trust, structural assurance, and e-commerce.